“Inter Arma Silent Musae”. Destroying Museums, Historical Buildings, and Monuments during the War in the Ukraine as War Crimes within the Meaning of International Law - Zawacka-Klonowska, Dominika; Główczewska, Aleksandra (Review of European and Comparative Law, 2023)
The article summarizes the situation related to the armed conflict in Ukraine in the context of the destruction of monuments and cultural objects as a war crime. The considerations relate to the provisions of international and European law, as well as to the positions developed by international case law. The stands of the international organization and community alongside the bodies of the European Union have been indicated. Poland’s efforts to help Ukrainian monuments are also discussed. Reference is made to the activities of the Polish Support Center for Culture in Ukraine established in Poland, within the structure of the National Heritage Institute and the Committee for Aid to Museums of Ukraine.